Sugar content of commonly eaten snack foods of school children in relation to their dental health status - Parajas, Irma L. (The Journal of the Philippine Dental Association)
Sugar is the principal substrate for micro-organisms causing dental caries. Yet it is impossible to eliminate sugar in the diet as almost all available foods particularly snack foods contain sugar. WHO recommended 10 kg. sugar or 27.40 gms. per person per year in non-fluoridated area and 15 kg. sugar/person year in non-fluoridated areas for low caries prevalence. The FFQ and 24-Hour Food recall of 824 rural and urban school children showed that all their snack foods are high in sugar except gelatine. Their sugar intake was three times more than the WHO recommended with a mean daily intake of 90 gms. for urban and 88 gms. of sugar for the rural. White sugar, hard calories, raisins, coco jam, and milk choco were the five most commonly eaten snack foods with high sugar content. Oral examination of the schoolchildren showed that dental caries was higher in the urban than in the rural. As a whole, the urban school children consumed more sugar and had higher dental carires compared to the rural schoolchildren. No significant correlation was found between sugar intake and dental caries.